UV-Visible Optical Absorbance of Graphene Oxide Synthesized from Zinc-Carbon Battery Waste via a Custom-Made Ultrasound Generator based on Liquid Sonication Exfoliation Method - Wisnuwijaya, Rhyko Irawan; Purwanto, Agus; Dwandaru, Wipsar Sunu Brams (Makara Journal of Science, 2017)
The objectives of this study are i) to synthesize graphene oxide (GO) from the waste materials of zinc-carbon (ZnC) batteries via the liquid sonication exfoliation (LSE) method using tweeter piezoelectric probes as speakers, and ii) to study the optical absorbance of the GO produced using a UV-Vis spectrophotometer by varying the mass of the graphite materials obtained from ZnC battery waste. The graphite materials are obtained from the carbon rods of the ZnC batteries, which are ground into powder. The powder is then mixed with distilled water, with powder mass variations of 0.4, 0.6, 0.8, and 1.0 grams. The solutions obtained are sonicated with a frequency of 30 kHz for six hours using a custom-made ultrasound generator based on piezoelectric probes. The effect of graphite material mass variation is studied by observing the UV-Vis spectrophotometer data before and after sonication. The results of this study show absorbance peaks at wavelengths of 221 nm to 227.5 nm, and shouldering peaks at 260 nm to 270 nm, indicating the presence of GO materials for all graphite mass variations. The best GO performances based on the UV-Vis results are obtained in samples with 0.8 and 1.0 grams of graphite powder, which undergo a red shift from 223.5 nm to 227.5 nm, respectively. Scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) are conducted upon the sample of 1.0 grams of graphite powder before and after sonication treatment. The SEM results before sonication show graphite materials forming in large chunks, whereas after sonication smaller islands of GO materials consisting of thin, transparent flakes are observed. The EDX results reveal that the sample material after sonication consists of 88% carbon, 11% oxygen, and a remaining 1% of aluminum, silicon, sulphur, ferrum, and zinc